Psoriasis and vitamin D: Insights from a randomised clinical trial, a cross-sectional analysis of the Tromsø Study 2015-16 and a factorial Mendelian randomisation study using the UK Biobank and HUNT - Jenssen, Marita (UiT The Arctic University of Norway, 2025)
Association between the skin disease psoriasis and lower serum 25-hydroxyvitamin D (25[OH]D) levels has been found in some studies. Overweight is considered a risk factor for both psoriasis and vitamin D deficiency. Topical vitamin D analogues are routine treatment for psoriasis, but effect of per oral supplementation is not established. This thesis aimed to enhance understanding of the link between serum 25(OH)D and psoriasis in the general population and explore the impact of overweight. Moreover, to investigate whether vitamin D supplementation has any place in the treatment of psoriasis. In a cross-sectional study using data from the population-based Tromsø7 study we found no statistically significant relationship between serum 25(OH)D and psoriasis, neither lifetime nor active disease. Interaction analyses indicated that high body mass index (BMI) and vitamin D deficiency combined increase the odds of active psoriasis more than the sum of the two, with an estimated 92% higher odds for active psoriasis in subjects with BMI >27.5 kg/m2 and 25(OH)D <25 nmol/L. In a randomised, double-blind placebo-controlled trial conducted through two winter seasons in Tromsø, we found no effect of vitamin D supplementation on psoriasis severity in subjects with lower serum 25(OH)D. Low baseline severity scores may explain the lack of a measurable effect. Surprisingly, serum 25(OH)D levels in the intervention group increased less-than-expected based on previous experimental data from the same source population, and this may have affected our results. To follow-up on our findings in Tromsø7, we performed a factorial Mendelian randomisation study using data from two independent population-based cohorts; the UK Biobank and the Trøndelag Health Study. We found no relative excess risk for psoriasis due to interaction between genetically predicted BMI and serum 25(OH)D. Considering the minor differences in actual BMI and serum 25(OH)D between the factorial groups small interaction effects may have been undetected. ...